The Implementation of Android-Based Gamification to Design an Interactive Quiz Educational Game for Support Learning Activities - Anwar; Andy Rachman; Faiz Muqorrir Kaaffah; Astried Silvanie; Syamsu Hidayat (Jurnal Sistim Informasi dan Teknologi, 2023)
Today's gadget technology has developed rapidly and has many features, along with the expansion of the internet network. In Indonesia alone, according to a survey from APJII, as much as more than 50% of the population has smartphone gadgets for daily use, and as much as more than 75% are dominated by children aged 12 years and over. However, only a few use smartphones for learning, which will affect smartphone users in terms of changing attitudes, behaviors, and motivation for learning. For this reason, the authors designed a quiz educational game application for learning, especially learning English, that utilizes gamification to increase children's motivation to learn while playing so they don't feel bored. The system was created using the GDLC development method with the Unity 3D Engine software, and for the Gamification system, using the Shephertz App42 API. Alpha testing shows that the functions in the game run well, and the gamification function works well and according to its function. The BETA test shows that the students taught by the author can improve their understanding of the English subject matter through the educational games made.